Social Determinants of Education in the Postmodern Society - Mühlpachr, Pavel (Wydawnictwo Naukowe Uniwersytetu im.Adama Mickiewicza w Poznaniu, 2013)
The situation of man in the beginning of 21st century is known as the postmodern. The concept of postmodernism indicates theoretically more or less elaborated opinions on current status of the process of globalization. The process of globalization does not produce only progress and positives but also threats, risks and transformation of man which are not only humanizing. The problem of postmodernism is mastery of plurality, heterogenity and otherness of ways, values and experiences of life, specialization of branches of science and societal development trends so that it contributes to dignified human life in society. The concept of postmodernism and its consequences for education of the younger generation project into conceptions of educational institutions, education in the family, but they also find their reflection in state policy due to the younger generation. Social changes, which occured at the end of 20th century, are part of global context of economical, political, social and cultural evolution. Their reach and importance must be seen into the future and in these wider connections.
Społeczne uwarunkowania edukacji w społeczeństwie ponowoczesnym
Keywords: education; postmodern society; globalization society